Stacked multi‐layer security for Hadoop distributed file system using HSCT steganography - Suganya, S.; Selvamuthukumaran, S. (Concurrency and computation, 2023)
Summary Big data needs to have scalable storage platforms as well as parallel processing environments. Hadoop is preferable because it is an open‐source software which works in a distributed, parallel processing environment and no need of any special hardware. In recent developments of Hadoop, security was introduced as optional. A symmetric block cipher advanced encryption standard (AES) is used for encryption. A 128 MB block of data needs 8 million encryptions. A better way of hiding the data from unauthorized access is preferable. Steganography, a more contemporary security technology than cryptography, is the art and science of hiding subconscious information in hidden item while exposing opponents their existence. The cover is an image, and the secret information may be a photo, music, video, or text. A double layer hexcode substituted–color space transformed (HSCT) steganography with 3 band splitting of data ensures confidentiality of the data and one time pad key generated with client's ID provides authentication also. Considering the volume of data, steganography concept is much faster than AES or any other cipher. Hiding the data inside the random images will indulge in fast reconstruction of data when needed for processing using either MapReduce or tools like spark.